Students’ health conditions and nursing intervention: experience report - Loraine Machado de Araújo; Lorena Machado de Araújo; Éricka Cecília Resende de Souza; Clélia Albino Simpson (Rev Rene)
This is a descriptive/exploratory study, aiming to describe students’ health conditions and report the experience of educational work related to personal and oral hygiene. Nursing consultations were conducted with 127 elementary level students from a school in Parnamirim/Rio Grande do Norte, from October to December 2009. The major health problems identified in the consultations were: poor hygiene, lice, mouth problems, low body mass index and irregular vaccination status. The educational activity involved group dynamics, educational video presentations, dialogical exhibition, leaflet distribution, personal hygiene kits, and tooth brush practice. Thus, a school health intervention is necessary for the promotion of knowledge and skills in health, contributing to the whole attention to the child.